118 Propensity Matched Analysis of Outcomes and Hospital Charges for Anterior vs Posterior Cervical Fusion for Cervical Spondylotic Myelopathy. (August 2015) - Tanenbaum, Joseph E.; Lubelski, Daniel; Rosenbaum, Benjamin P.; Benzel, Edward C.; Mroz, Thomas
Abstract : INTRODUCTION: Anterior cervical fusion (ACF) and posterior cervical fusion (PCF) are 2 common surgical treatments for cervical spondylotic myelopathy (CSM). It is unclear whether ACF or PCF is superior with regard to charges or outcomes for the treatment of CSM. The goal of the present study is to help guide clinical decision making when choosing between ACF and PCF in treating CSM. METHODS: We used Nationwide Inpatient Sample data to compare ACF with PCF in the management of CSM. We included all patients with a diagnosis of CSM between 1998 to 2011 who were 18 years or older. ACF patients were matched to PCF patients by using propensity scores that were based on patient characteristics (number of levels fused, spine alignment, comorbidities), hospital characteristics, and patient demographics. Multivariate regression was used to measure the effect of treatment assignment on in-hospital charges, length of hospital stay, in-hospital mortality, discharge disposition, and dysphagia diagnosis. RESULTS: From 1998 to 2011, we identified 109728 hospitalizations with a CSM diagnosis. Of these patients, 45629 (41.6%) underwent ACF and 14439 (13.2%) underwent PCF. The PCF cohort incurred an average of $41683 more in-hospital charges ( P < .001, inflation adjusted to 2011 dollars) and remained in hospital an average of 2.4 days longer ( P < .001) than the ACF cohort. The ACF cohort was just as likely to die in the hospital (OR 0.91, 95% CI 0.68-1.2), 3.0 times more likely to be discharged to home or self-care (95% CI 2.9-3.2), and 2.5 times more likely to experience dysphagia (95% CI 2.0-3.1) than the PCF cohort. CONCLUSION: In treating CSM, ACF led to lower hospital charges, shorter hospital stays, and an increased likelihood of being discharged to home relative to PCF.